Application of Balinese Cultural Concepts in the Creation of Neo-Traditional Tattoo Art Works - Mahananda, I Putu Gede Rindra; Pemayun, Tjokorda Udiana Nindhia; Putra, I Gede Jaya (Program Studi Seni Murni ISI Bali, 2024)
This thesis contains a description of the creation of works of tattoo art with the theme